Analysis Of The Relationship Between Social Support Of Correctional Officers And The Subjective Well-Being Of Inmates In Class IIA Correctional Institution Kotabumi - Tegar Aria Taba; Markus Marselinus Soge (International Journal Labs, 2024)
This study aims to analyze the relationship of social support provided by correctional officers to the subjective well-being of inmates in the Class IIA Kotabumi Correctional Institution. The social support received by the inmates, whether in the form of emotional, instrumental, informational, or reward support, is thought to have a significant effect on their subjective feelings of well-being. This study uses a quantitative approach with survey and questionnaire methods as data collection instruments. The sample of this study is inmates in the Class IIA Kotabumi Prison who are randomly selected. Data analysis was carried out using the Pearson correlation test to test the relationship between social support variables and subjective well-being. The results of the study are expected to provide insight into the importance of the role of correctional officers in improving the psychological welfare of inmates and provide recommendations for more humane correctional institution management policies.